Employee Development Strategies, Organizational Culture, And The Use Of HRM Technology In Building Organizational Trust: The Role Of Employee Engagement Interventions - Ilzar Daud (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study explores the intricate relationships among employee development strategies, organizational culture, HRM technology, organizational trust , and employee engagement  at PT Tanjungpura Lintas Borneo. Through a sample of 60 employees, the research employs Structural Equation Modeling (SEM) with the SmartPLS software. The results reveal that effective employee development strategies significantly influence organizational trust and subsequent employee engagement. A positive organizational culture demonstrates a strong and significant impact on both trust and employee engagement. However, the utilization of HRM technology does not exhibit a statistically significant association with organizational trust and employee engagement at the current stage. This nuanced finding suggests the need for further exploration and optimization of HRM technology initiatives. The study underscores the complexity of organizational dynamics and advocates for a comprehensive approach to cultivate a workplace environment conducive to trust, engagement, and overall organizational success at PT Tanjungpura Lintas Borneo.